Contributions of the immune system to the pathophysiology of traumatic brain injury – evidence by intravital microscopy - Schwarzmaier, Susanne M.; Plesnila, Nikolaus (Frontiers in Cellular Neuroscience, 2014)
Traumatic brain injury (TBI) results in immediate brain damage that is caused by the mechanical impact and is non-reversible. This initiates a cascade of delayed processes which cause additional – secondary – brain damage. Among these secondary mechanisms, the inflammatory response is believed to play an important role, mediating actions that can have both protective and detrimental effects on the progression of secondary brain damage. Histological data generated extensive information; however, this is only a snapshot of processes that are, in fact, very dynamic. In contrast, in vivo microscopy provides detailed insight into the temporal and spatial patterns of cellular dynamics. In this review, we aim to summarize data which was generated by in vivo microscopy, specifically investigating the immune response following brain trauma, and its potential effects on secondary brain damage.